2011
DOI: 10.1186/1475-2859-10-98
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of antibiotic activity of Xenorhabdus bovienii by medium optimization using response surface methodology

Abstract: BackgroundThe production of secondary metabolites with antibiotic properties is a common characteristic to entomopathogenic bacteria Xenorhabdus spp. These metabolites not only have diverse chemical structures but also have a wide range of bioactivities with medicinal and agricultural interests such as antibiotic, antimycotic and insecticidal, nematicidal and antiulcer, antineoplastic and antiviral. It has been known that cultivation parameters are critical to the secondary metabolites produced by microorganis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 39 publications
5
82
1
2
Order By: Relevance
“…Herein, the purified metabolite was isolated from saltpan bacteria and its maximum anti-MRSA activity was attained by optimizing the culture condition in ZMB broth. It has been reported that the culture optimization in media using different parameters including temperature, pH, incubation period, carbon and nitrogen sources influenced the production of the antimicrobial compound [28]. In the current study, the nutritional and environmental parameters were optimized in ZMB medium for the efficient production of anti-MRSA compound.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, the purified metabolite was isolated from saltpan bacteria and its maximum anti-MRSA activity was attained by optimizing the culture condition in ZMB broth. It has been reported that the culture optimization in media using different parameters including temperature, pH, incubation period, carbon and nitrogen sources influenced the production of the antimicrobial compound [28]. In the current study, the nutritional and environmental parameters were optimized in ZMB medium for the efficient production of anti-MRSA compound.…”
Section: Discussionmentioning
confidence: 99%
“…The predicted data from the model are in agreement with the observed one as is evident from the figure. Figure 4 shows the normal plot of residuals, the linear pattern indicating normality in the error term [24]. A plot of residuals versus the predicted response is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to achieve high product yields from the selected NF15 isolate, it was necessary to design a proper production medium for an efficient fermentation process (16, 29). Fungal isolates showed better growth and antimicrobial potential in SDB compared to the other media.…”
Section: Discussionmentioning
confidence: 99%